Implicaciones éticas de la IA y su potencial impacto en el derecho internacional - Almache Barreiro, Juan Carlos (2023)
The relevance of modeling the moral and ethical aspects that regulate the resulting dialectic between Artificial Intelligence (AI) and the forensic regime that must legislate it, identifies a dispersion and legal destructuring regarding the use and application of its programming, learning protocols and introduction of the human rights that, in the face of the moral values of their decision-making in the face of this crucial scenario, are developed legislatively in the legal systems of nations. The objective of this research was to approximate the criteria of international legal responsibility that included principles of humanity and public conscience in the computational programming of AI. The methodology used was qualitative, applying documentary research from the historical method (legal studies with bibliographic references), logical examination (description of the phenomenon in development) and legal-comparative analysis (confluence of contemporary regulations), managing to identify an ineffective control of the algorithmic bias of the AI, and possibilities of discretionary subjectivity of its programmers with real consequences, including human integrity, which it is called to serve and protect, as well as the need to build criteria of international legal responsibility with respect to the before cited principles in AI computational programming.